Answer:
B. x = 3
Explanation:
Simplifying
4 + 3x = 2(3x + -7) + 9
Reorder the terms:
4 + 3x = 2(-7 + 3x) + 9
4 + 3x = (-7 * 2 + 3x * 2) + 9
4 + 3x = (-14 + 6x) + 9
Reorder the terms:
4 + 3x = -14 + 9 + 6x
Combine like terms: -14 + 9 = -5
4 + 3x = -5 + 6x
Solving
4 + 3x = -5 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
4 + 3x + -6x = -5 + 6x + -6x
Combine like terms: 3x + -6x = -3x
4 + -3x = -5 + 6x + -6x
Combine like terms: 6x + -6x = 0
4 + -3x = -5 + 0
4 + -3x = -5
Add '-4' to each side of the equation.
4 + -4 + -3x = -5 + -4
Combine like terms: 4 + -4 = 0
0 + -3x = -5 + -4
-3x = -5 + -4
Combine like terms: -5 + -4 = -9
-3x = -9
Divide each side by '-3'.
x = 3
Simplifying
x = 3